Acute exposure to essential amino acids activates contraction mediated mTOR/p70 signaling in soleus muscle of elderly rats - Mascaro, A.; d'Antona, G. (Progress in Nutrition, 2013)
The aging process leads to sarcopenia that is a progressive skeletal muscle weakening due to reduction of mass and concomitant change in phenotype. Several studies indicate that amino acids supplementation and, in particular, branched chain amino acids (BCAA) and contraction may activate protein synthesis through the activation of mTOR/ p70S6K signaling pathway. In the present study we used an in vitro assay to analyze the effects of tetanic contractions and acute exposure to branched chain enriched amino acid mixture on mTOR/ p70S6K signaling activation in soleus muscle of elderly rats. Methods:  Soleus muscles from Wistar male elderly rats (18 mo of age) were grouped as follows (n = 5 each): nc, not contracted; C, contracted (10 tetani of 0.5 sec/100Hz at 0.02Hz) and contracted and acutely incubated with BCAA enriched mixture at 1% (C+BCAA). Following treatment the activation level of mTOR and p70S6K was measured by Western blot. Results: Contracted muscles (C) showed no increase of mTOR activation relative to uncontracted muscles (nc)  and a significant increase of the level of p70S6K activation (+80%). On the contrary  following acute BCAA enriched mixture exposure contracted muscles displayed higher mTOR activation  (Figure 1) in comparison with C  and nc muscles (+40%) and a further increase  in p70S6K in comparison with C (+180% vs nc and +55% vs C). Conclusions: Tetanic contractions and acute exposure to BCAA enriched mixture are able to synergically activate the  mTOR/p70S6K signalling pathway in the soleus muscle of elderly rats.